Allelopathic Effect of Cyperus rotundus L. on Seed Germination and Initial Growth of Glycine max L. cv. Grobogan - Darmanti, Sri; Santosa, Santosa; Dewi, Kumala; Nugroho, L Hartanto (Bioma : Berkala Ilmiah Biologi, 2015)
Allelopathy is a phenomenon of direct or indirect, beneficial or adverse effects of a plant on its own or another plant through the release of chemicals into the environment. This experiment was carried out to determine the allelopathic effect of Cyperus rotundus L. (purple nutsedge) tuber aqueous extract on seed germination and initial growth of Glycine max L. (soybean) seedlings. The experiment was performed in completely randomized (CRD) design with five replications, using a range of concentrations of aqueous tuber extracts of nutsedge, i.e.: 0%, 5%, 10%, 15%, 20% and 25%. The petri dish experiment showed that with increase of the tuber extract concentration, a significant increase was noted in mean germination time (MGT), significant decreases in germination index (GI), growth tolerance index (GTI), wet weight seedling, dry weight seedling andÂ  length of soybean seedling.Â Â